5. Penerapan Strategi Bauran Pemasaran Terhadap Peningkatan Frekuensi Penumpang - Arif Fakhrudin (Sekolah Tinggi Teknologi Kedirgantaraan, 2019)
Promotion is carried out by the company with the aim of providing information, influencing, persuading and encouraging consumers to make purchases of goods or services that are marketed. With the promotion, the company hopes to increase sales in accordance with the targets set. For this reason, a marketing strategy is needed, namely by implementing the right promotional mix so that the company's goals can be achieved. The writing method used in this study is a qualitative method where the author describes the promotion strategy in increasing the frequency of passengers. The data used in this study are primary data and secondary data taken and reprocessed from interviews by employees of PT. Citilink Palangkaraya and passenger data at the Tjilik Riwut Palangkaraya Air Transportation office based on departures and arrivals every month in 2017 and 2018. The results of this thesis show that there is an increase in passengers per three months, namely in January - March in 2017 and 2018 by the Citilink Indonesia airline Palangkaraya district, with the activities and implementation of promotional strategies namely direct advertising and face-to-face sales get maximum results with these activities, the increase in the frequency of Citilink passengers, namely January-March 2017 and 2018 increased by 14%.